Has China’s coal consumption really peaked?—Prediction and scenario analysis of China’s coal consumption peak under the double-carbon target - Wang, Wensheng; Kao, Xiaoxuan; Lin, Zhihan; Zhang, Yue (Frontiers in Environmental Science, 2022)
This paper presents a scenario study of China's peak coal consumption in the context of the Double-Carbon strategy. Using the method of system dynamics theory to analyze the peak coal consumption under 9 sub-scenarios. The results show that: The peak of coal consumption in China can echo the strategic goal of peaking carbon in 2030, which is in line with the laws of reality. The economic growth rate has the greatest influence on the coal consumption peak, followed by industrial structure and coal consumption intensity, and the population growth rate has the least influence. The SD3 scenario is the optimal path for China’s future coal consumption development. Under this scenario, coal consumption will peak at 437.8 million tons in 2027. If the future energy consumption trend is close to SD3 scenario, the socioeconomic growth rate will slow down obviously, the population growth rate will slow down, the industrial structure optimization degree will be higher, and the intensity of coal consumption will be lower. The coal consumption peak varies greatly according to different development goals and transformation dynamics. Under the constraints of the established peak time, the scenario of coal consumption peak has a variety of combinations.